Cryo-EM structure of the monomeric Rhodobacter sphaeroides RC–LH1 core complex at 2.5 Å. Issue 20 (29th October 2021) - Qian, Pu; Swainsbury, David J.K.; Croll, Tristan I.; Salisbury, Jack H.; Martin, Elizabeth C.; Jackson, Philip J.; Hitchcock, Andrew; Castro-Hartmann, Pablo; Sader, Kasim; Hunter, C. Neil
Abstract : Reaction centre light-harvesting 1 (RC–LH1) complexes are the essential components of bacterial photosynthesis. The membrane-intrinsic LH1 complex absorbs light and the energy migrates to an enclosed RC where a succession of electron and proton transfers conserves the energy as a quinol, which is exported to the cytochrome bc 1 complex. In some RC–LH1 variants quinols can diffuse through small pores in a fully circular, 16-subunit LH1 ring, while in others missing LH1 subunits create a gap for quinol export. We used cryogenic electron microscopy to obtain a 2.5 Å resolution structure of one such RC–LH1, a monomeric complex from Rhodobacter sphaeroides. The structure shows that the RC is partly enclosed by a 14-subunit LH1 ring in which each αβ heterodimer binds two bacteriochlorophylls and, unusually for currently reported complexes, two carotenoids rather than one. Although the extra carotenoids confer an advantage in terms of photoprotection and light harvesting, they could impede passage of quinones through small, transient pores in the LH1 ring, necessitating a mechanism to create a dedicated quinone channel. The structure shows that two transmembrane proteins play a part in stabilising an open ring structure; one of these components, the PufX polypeptide, is augmented by a hitherto undescribed protein subunit we designate as protein-Y, which lies against the transmembrane regions of the thirteenth and fourteenth LH1α polypeptides. Protein-Y prevents LH1 subunits 11–14 adjacent to the RC QB site from bending inwards towards the RC and, with PufX preventing complete encirclement of the RC, this pair of polypeptides ensures unhindered quinone diffusion.